Evaluating sprinting ability, density of acceleration, and speed dribbling ability of professional soccer players with respect to their positions - Taskin, H. (The Journal of Strength and Conditioning Research, 2008)
The aim of this study is to evaluate sprinting ability, density of acceleration, and speed dribbling ability of professional soccer players with respect to their positions. A total of 243 professional soccer players were examined. These soccer players are playing in different leagues of Turkey. The F-MARC test battery, which was designed by FIFA, was used for soccer players. We did not find any statistical differences for 30-m sprint test and four-line sprint test values with respect to positions of soccer players (p > 0.05). On the other hand, there was a statistical difference for speed dribbling test values in terms of positions of soccer players (p < 0.05). It was found that the test values of defense players, midfielders, and forwards were better than the test values of goalkeepers (p < 0.05). In conclusion, this study, which was done during the training season, shows that there is a similarity between the abilities of professional soccer players for 30-m sprint and four-line sprint tests. Therefore, it is believed that there must be fast players in all positions in terms of sprint ability. There is a similarity among defenders, midfielders, and forwards in terms of speed dribbling ability; in contrast, the speed dribbling ability of goal keepers is different from the players in those three positions. Although there are many more speed dribbling exercises within the training programs of defenders, midfielders, and forwards, the speed dribbling ability test is not used much for goal keepers. Correspondingly, speed dribbling ability is not a specific indicator for goal keepers, and this test should not be used for the choice of goalkeepers.